2020
DOI: 10.1080/14786419.2020.1737056
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antitumor and antioxidant effects of four lebanese plants extracts on human pulmonary adenocarcinoma

Abstract: All samples were collected in full flowering stage. The plant identification was based on 'Nouvelle Flore du Liban et de la Syrie' by Paul Mouterde and voucher specimen were deposited at the Herbarium of the Faculty of Agricultural Sciences -USEK with their numbers. Prangos asperula (MNII 265a) and Hirtellina lobelii (MNIII 145b) were collected from "Tannourine" region in the North of Lebanon, Salvia multicaulis ((MNIII 475a) was collected from "Mdayrej" (Zahleh region) and Stachys ehrenbergii (MNIII 235c) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…japonica exhibited antioxidant effects on ultraviolet A (UVA)-irradiated human dermal fibroblasts (HDFs), through suppression of ROS generation [ 160 ]. The antioxidant activity of the methanol extract of the Lebanese species S. ehrenbergii was measured by ABTS radical cation decolorization assay and the methanol extract showed an IC 50 value of 52 ± 7.5 mg/mL [ 154 ]. Furthermore, the chemical profile and some biological activities of three herbal teas in Anatolia were examined [ 84 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…japonica exhibited antioxidant effects on ultraviolet A (UVA)-irradiated human dermal fibroblasts (HDFs), through suppression of ROS generation [ 160 ]. The antioxidant activity of the methanol extract of the Lebanese species S. ehrenbergii was measured by ABTS radical cation decolorization assay and the methanol extract showed an IC 50 value of 52 ± 7.5 mg/mL [ 154 ]. Furthermore, the chemical profile and some biological activities of three herbal teas in Anatolia were examined [ 84 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…They reported that all the plant extracts induced DNA damage, using the comet assay, whereas the extract of S. officinalis induced the increase of sister chromatid exchange value. The methanol extract of the Lebanese species S. ehrenbergii was investigated for its antioxidant and cytotoxic activity [ 154 ]. The cytotoxicity was examined by MTT assay where the methanol extract showed the highest cytotoxicity (IC 50 = 420 ± 104 μg/mL) at a concentration of 3000 mg/mL.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Indeed, FLS is a significant source incorporated in the production of different MMPs [3,7]. Therefore, according to experimental in vitro studies, one can assume that SSC and other Stachys, when they have exhibited antiproliferative and pro-apoptotic effects [22,[31][32][33], might reduce the number of FLSs and likely help to modulate the levels of MMP production in FLSs [5,8]. Findings of the current randomized clinical trial are only representative (generalizability of data) to a group of RA patients who have 3.2≤DAS28≤5.1 in terms of inferring the moderate activity of RA disease.…”
Section: The Initial and Final Values Are Reported As Mean±standard Deviation (Sd)mentioning
confidence: 99%
“…The anti-inflammatory potential of SSC could be partly explained by inhibiting some enzymes (e.g., cyclooxygenase and lipoxygenase) [16,30]. Critical to this, the anti-proliferative activities of Stachys is another implication that has been emerged by in vitro studies [31][32][33],…”
Section: Introductionmentioning
confidence: 99%
“…multicaulis and H. lobelia, have antitumor and antioxidant effects on human pulmonary adenocarcinoma cells (Abi-Rizk et al, 2020). Still, more studies need to be conducted to prove the medicinal benefits of Lebanese natural products.…”
Section: Lebanese Natural Remediesmentioning
confidence: 99%